2017
DOI: 10.1177/014556131709600901
|View full text |Cite
|
Sign up to set email alerts
|

Intracapsular Tonsillectomy for Keratosis Pharyngeous: A Pilot Study of Postoperative Recovery and Surgical Efficacy

Abstract: Our objective was to perform a pilot study comparing intracapsular radiofrequency ablation tonsillectomy with subcapsular tonsillectomy in adult patients with keratosis pharyngeous. Patients diagnosed with keratosis pharyngeous between December 2010 and February 2013 were randomized to undergo either intracapsular or subcapsular tonsillectomy using radiofrequency ablation. Postoperative pain scores and amount of pain medication taken were recorded for 2 weeks. A 6-month follow-up questionnaire was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…19 Gaudreau et al noted no cases of dehydration postoperatively in either group. 27 There were no recorded Clavien Dindo grade IV to V serious complications.…”
Section: Analgesia Requirement Analgesia Requirement Wasmentioning
confidence: 90%
See 4 more Smart Citations
“…19 Gaudreau et al noted no cases of dehydration postoperatively in either group. 27 There were no recorded Clavien Dindo grade IV to V serious complications.…”
Section: Analgesia Requirement Analgesia Requirement Wasmentioning
confidence: 90%
“…19 Appropriate blinding of outcome assessors occurred in six studies. 14,[22][23][24]26,27 Incomplete outcome data. Two trials reported no post-randomization drop-outs and all patients that received treatment were followed-up.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations